Aplikasi Sensor Suhu Lampu Yang Dikendalikan Menggunakan Smartphone Android - Harlan Effendi; Bima Cucu Riswara (Institut Sains dan Teknologi Nasional, 2016)
This research describes the control system for the lights in smart home technology. In this case, the control system use the temperature measurements that are generated when light is on. With this control system, smart home technology users will easily find out the condition of the lights are switched on remotely or switched off. In the condition of the lights on, the temperature indication will show the value go up and in a state of light off the temperature indication will indicate a fixed value. In this research, the system will use Bluetooth technology as a media command without cable. This command will be sent from the smart phone to the Arduino Uno microcontroller. The LM 35 temperature sensor will transmit the temperature indications are legible to smartphones via Bluetooth. The application of temperature sensor is for returning a signal from the state of the lights in the smart home applications.